Arabidopsis COP8, COP10, and COP11 genes are involved in repression of photomorphogenic development in darkness. - Wei, N (1994)
Wild-type Arabidopsis seedlings are capable of following two developmental programs: photomorphogenesis in the light and skotomorphogenesis in darkness. Screening of Arabidopsis mutants for constitutive photomorphogenic development in darkness resulted in the identification of three new loci designated COP8, COP10, and COP11. Detailed examination of the temporal morphological and cellular differentiation patterns of wild-type and mutant seedlings revealed that in darkness, seedlings homozygous for recessive mutations in COP8, COP10, and COP11 failed to suppress the photomorphogenic developmental pathway and were unable to initiate skotomorphogenesis. As a consequence, the mutant seedlings grown in the dark had short hypocotyls and open and expanded cotyledons, with characteristic photomorphogenic cellular differentiation patterns and elevated levels of light-inducible gene expression. In addition, plastids of dark-grown mutants were defective in etioplast differentiation. Similar to cop1 and cop9, and in contrast to det1 (deetiolated), these new mutants lacked dark-adaptive change of light-regulated gene expression and retained normal phytochrome control of seed germination. Epistatic analyses with the long hypocotyl hy1, hy2, hy3, hy4, and hy5 mutations suggested that these three loci, similar to COP1 and COP9, act downstream of both phytochromes and a blue light receptor, and probably HY5 as well. Further, cop8-1, cop10-1, and cop11-1 mutants accumulated higher levels of COP1, a feature similar to the cop9-1 mutant. These results suggested that COP8, COP10, and COP11, together with COP1, COP9, and DET1, function to suppress the photomorphogenic developmental program and to promote skotomorphogenesis in darkness. The identical phenotypes resulting from mutations in COP8, COP9, COP10, and COP11 imply that their encoded products function in close proximity, possibly with some of them as a complex, in the same signal transduction pathway.